Teratoid Wilms Tumor and Classical Wilms Tumor: A Retrospective 10-Year Single-Center Study and Literature Review - Wu, Wei; Wu, Yibo; Xu, Weijue; Liu, Jiangbin; Lv, Zhibao (Frontiers in Surgery, 2022)
Background One of the most prevalent forms of renal tumors detected among pediatric patients is the Wilms tumor (WT). Teratoid WT is a rare WT subclassification that is characterized by teratoma-like characteristics that include the features of many diverse tissue categories. Less than 70 teratoid Wilms tumor (TWT) cases have been explained up to now. Methods Between 2010 and 2020, patients with classical WT and TWT admitted to our hospital were included in this study. Clinicopathological characteristics, intraoperative findings, histopathological parameters, and prognostic outcomes were then compared between classical WT and TWT. To compare these variables, TWT and WT cases were matched at a 1:3 ratio. Results A total of 67 total WT cases, i.e., five diagnosed with TWT, were enrolled. While no significant differences in analyzed variables were detected between these groups, tumor volumes were notably larger in the TWT group relative to the classical WT group (203.30 ± 109.89 vs. 104.30 ± 66.97 cm3) despite similar tumor weight values in both groups (471.00 ± 80.65 vs. 432.67 ± 109.25 g). As for five patients diagnosed with TWT, all were alive during the follow-up, while one of them was diagnosed with pelvic metastasis. Conclusions This study is the first to our knowledge to have reported on the incidence of TWT among Chinese children, and our results preliminarily suggest that a combination of surgery and chemotherapy may be appropriate for the treatment of patients with WT, although prognostic outcomes varied substantially among patients with different stages of the disease. TWT tumor density may be lower than classical WT tumor density. Further research regarding the basic biological characteristics of TWT and relevant theranostic markers associated with this tumor type is warranted to better guide the development of individualized treatments for this rare cancer type.